2010
DOI: 10.1007/s00259-010-1604-0
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for 11C-choline PET/CT in the early detection of metastatic disease in surgically treated prostate cancer patients with a mild PSA increase <1.5 ng/ml?

Abstract: In our study, (11)C-choline PET/CT was able to detect recurrent disease in 28% of the patients with mild biochemical relapse characterized by very low trigger PSA levels (PSA <1.5 ng/ml). Very interestingly (11)C-choline PET/CT detected distant unexpected metastases in 21% of the patients. At multivariate statistical analysis only PSAdt and node status were shown to be significant and independent predictive factors for positive (11)C-choline PET/CT. Therefore, (11)C-choline could be suggested to be performed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
92
2
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(112 citation statements)
references
References 25 publications
8
92
2
10
Order By: Relevance
“…in the group of hormone-resistant patients with PCa. Similar findings were obtained by Castellucci et al in 102 patients with PSA levels below 1.5 ng/ml [22]. Other studies that have shown a positive detection rate of the technique in both subgroups of patients, consistently showed higher percentage values in hormone-resistant patients than in hormone-sensitive patients [21,[23][24][25][26].…”
supporting
confidence: 78%
See 1 more Smart Citation
“…in the group of hormone-resistant patients with PCa. Similar findings were obtained by Castellucci et al in 102 patients with PSA levels below 1.5 ng/ml [22]. Other studies that have shown a positive detection rate of the technique in both subgroups of patients, consistently showed higher percentage values in hormone-resistant patients than in hormone-sensitive patients [21,[23][24][25][26].…”
supporting
confidence: 78%
“…In this group of patients there are currently no available data derived from paired studies. However, useful information has been obtained from cross-sectional studies including a relatively large number of hormonesensitive and hormone-resistant patients in which the two groups were contrasted either semiquantitatively or by appropriate statistical analysis (logistic regression) [21,22].…”
mentioning
confidence: 99%
“…at PSA levels below 1-1.5 ng/mL (3,7,32,33). Thus, 68 Ga-PSMA ligand PET/CT improves lesion detectability in the group of patients at an early state, potentially allowing more tailored salvage therapies.…”
Section: Discussionmentioning
confidence: 99%
“…30-40% [13] [16]. Even though localized treatment of distant metastases currently is not an established therapy several reports have already been published, showing promising results regarding CH-PET/CT guided radiation therapy and salvage surgery [17][18][19].…”
Section: Introductionmentioning
confidence: 99%